Effect of corn endosperm type and corn containing the Cry1F protein on performance of beef heifers fed finishing diets based on steam-flaked corn - Sindt, J.J.; Loe, E.R.; Kessen, T.J.; Sulpizio, M.J.; Montgomery, Sean P.; Owens, F.N.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty beef heifers (initial body weight = 795 ± 18 lb) were individually fed finishing diets based on steam-flaked corn for 118 days. Dietary treatments consisted of corn hybrids containing vitreous (HARD), opaque (SOFT), or intermediate (INT) types of corn endosperm. Within the HARD endosperm type, a transgenic hybrid (HARD-GMO) containing the Herculex I Cry1F protein was compared with its nontransgenic, conventional (HARDCONV) counterpart. Dry matter intake, average daily gain, and gain efficiencies were similar among treatments. Likewise, hot carcass weight, dressing percentage, and ribeye area were unaffected by dietary treatment. Heifers fed HARD-CONV were fatter than heifers fed HARD-GMO, having fewer (P<0.01) USDA Yield Grade 1 and 2 carcasses. In this experiment, feeding flaked corn finishing diets that contained different endosperm types did not alter performance or carcass characteristics. Feeding heifers HARD-GMO compared with HARD-CONV corn resulted in similar performance, although heifers fed HARD-CONV had higher USDA Yield Grades, perhaps because of greater starch availability of HARD-CONV flaked corn than HARD-GMO corn.
Keywords: Beef; Herculex I Cry1F protein; Corn endosperm; Steam-flaked corn; Heifers